Moços de hoje, dirigentes da nação amanhã: a história do esporte universitário no Brasil de 1930 a 1941 - Vitor Lucas de Faria Pessoa (2018)
This work seeks to elucidate the trajectory of university sports in Brazil from 1930 to 1941, a period that corresponds to the systematization of the phenomenon in Brazilian universities and after its rigging by the Estado Novo. The objectives of the dissertation are to seek indications of the systematization of university sports in Brazil, seeking to highlight which institutions and actors were responsible for its development in the country. Analyze the involvement of the student movement with academic sports. Observe how university sport was used as a privileged space for the affirmation of identities, and finally, to understand his role in the discussions about amateurism and professionalism in sports from the 1930s onwards. Thus, in order to achieve the proposed objectives, we used documents and periodicals dating from 1930 until 1941. The collection of the sources was done in the collection of the Biblioteca Nacional do Rio de Janeiro, through the Brazilian Digital Library. It was verified that student associativism was the main factor that contributed to the systematization of university sports in Brazil. The articulating forums of the Brazilian student movement, such as the União Nacional dos Estudantes congresses, as well as the assemblies of grassroots organizations, were fundamental for university sports to be conceived as a factor that would contribute to a greater exchange among Brazilian academics. The Estado Novo used university sports as a vehicle for propaganda of nationalist ideals. Throughout the decade of 1930, Vargas would approach more and more of the academic institutions, being that the definitive appropriation of the Brazilian Confederation of University Sports occurred with the promulgation of the Decree-law nº 3,617 in 15 of September of 1941. In addition, the university sport was conceived as a refuge for the defenders of amateurism, a kind of counterpoint to the process of professionalization of football that occurred during the same period in which university sports consolidated in the country.